EFFECT OF VIEWING ANGLE OF IR THERMOGRAPHY CAMERA FOR THE DETECTION OF LANDMINE - Moustafa M. Kurdi (Системный анализ и прикладная информатика)
The detection and recognition of sub-surface buried objects, such landmines, with variable characteristics may be extremely difficult. Infrared (IR) thermography, which is widely employed in the detection of discontinuities in materials and structures, would be in principle suitable also for this kind of application. The issue in this case appears to be the presence of excessive levels of background noise, whose modelling is difficult, in that it results from a number of factors e.g., moisture content, presence of vegetation, and variation of solar radiation at topsoil level. In recent years, a number of studies have tried to overcome these limitations and improve the reliability of this method, using filtering and automatic pattern recognition techniques, specific for the detection of buried objects. This work is aimed at revising and commenting the most recent experiences in this application of IR thermography. The article considers the possibility of using an IR thermal imaging camera attached to a multifunctional quadrocopter in order to improve the reliability of detection of ground and buried explosive objects.